Analyzing Sentiment Trends and Patterns in Bitcoin-Related Tweets Using TF-IDF Vectorization and K-Means Clustering - Tri Wahyuningsih; Shih Chih Chen (Journal of Current Research in Blockchain, 2024)
This study conducts a comprehensive analysis of Bitcoin-related tweets to understand sentiment trends and patterns using TF-IDF vectorization and K-means clustering. The dataset, comprising 1,544 unique tweets, was collected via the Twitter API and preprocessed to remove duplicates and clean the text. Sentiment analysis revealed a distribution of 53.7% neutral, 29.7% positive, and 16.6% negative tweets, indicating a predominant neutral sentiment in the discourse. Keyword analysis identified frequent terms such as 'bitcoin' (479 occurrences), 'new' (46), 'good' (43), 'crypto' (39), and 'trade' (39). Visualizations through word clouds highlighted the specific language associated with each sentiment category, with positive tweets focusing on opportunities and innovation, while negative tweets emphasized risks and scams. Cluster analysis using K-means, with the optimal number of clusters determined by the elbow method, resulted in three distinct clusters. Cluster 0, comprising 1,346 tweets, was characterized by neutral and informative content, focusing on market updates and trading strategies. Cluster 1, with 163 tweets, contained a higher concentration of positive sentiment, highlighting positive developments and investment opportunities. Cluster 2, the smallest with 35 tweets, focused on negative sentiment, reflecting concerns about market volatility and fraudulent activities. These clusters provided a nuanced understanding of the thematic composition of Bitcoin-related tweets. The study's findings have practical implications for investors, traders, and market analysts by providing insights into market mood and sentiment trends. The integration of these findings into predictive models can enhance market prediction accuracy and develop more effective trading strategies. Despite the study's contributions, limitations such as the dataset's language and scope suggest areas for future research, including real-time sentiment analysis and the incorporation of multimodal data sources. This research advances the field of sentiment analysis in financial markets, particularly within the context of cryptocurrencies, by offering a detailed and longitudinal examination of social media sentiment.